The bitter taste of hope : ideals, ideologies, and interests in the age of Obama - Bronner, Stephen Eric, 1949- (State University of New York Press, 2017)
President Barack Obama was elected to office on a wave of hope. With his tenure as President of the United States now concluded it is time to take stock of his record at home and abroad. The Bitter Taste of Hope is a collection of essays that critically evaluate America's domestic landscape on the one hand, particularly new social movements, and the nation's foreign policy, particularly in the Middle East, on the other. Stephen Eric Bronner engages a wide-ranging set of political and ideological conflicts that defined the "Age of Obama," especially the most pressing international concerns that have developed in accord with an increasingly globalized world. Bronner illuminates not only well-known events like the American involvement in Afghanistan and Iraq, the plight of the Palestinians, and the Arab Spring but also matters about which the general public knows little such as the national hopes of the Circassians, the complexities of Sudan, and the pitiful existence endured by the Coptic Christians of Cairo. Clearly written, lively in its style, interdisciplinary in conception and timely in its message, The Bitter Taste of Hope will undoubtedly prove required reading for activists and academics alike.
Keywords: Obama, Barack.; Obama, Barack; United States -- Politics and government -- 2009-2017.; United States -- Foreign relations -- 2009-2017.; United States -- Foreign relations -- Middle East.; Middle East -- Foreign relations -- United States.; États-Unis -- Politique et gouvernement -- 2009-2017.; États-Unis -- Relations extérieures -- 2009-2017.; États-Unis -- Relations extérieures -- Moyen-Orient.; Moyen-Orient -- Relations extérieures -- États-Unis.; HISTORY -- United States -- State & Local -- General.; Diplomatic relations; Politics and government; Middle East; United States; 2009-2017; Electronic books.